Development of Interactive Website-Based Learning Media with the Assistance of Educandy on the Periodic Table of Elements Material - Sari Sari; Latifa Amaliah; Risa Rahmawati S; Silmi Rahma Amelia (International Journal of Learning Media on Natural Science (IJLENS), 2026)
ABSTRACT Learning the periodic table of elements is often perceived as difficult because it involves abstract concepts, symbolic representations, and multiple relationships among elements that students must understand. This study aimed to develop interactive web-based learning media for periodic table material by integrating the Carrd platform with Educandy and to examine its validity and feasibility at the development stage. The study employed a Research and Development approach using the ADDIE model up to the development phase. The product was validated by five expert validators consisting of lecturers and chemistry teachers, and its feasibility was tested with 15 tenth-grade students at SMAN 1 Banjaran. The validation results showed an average score of 0.85, which was categorized as very high. Across aspects, the scores included software engineering (0.864), visual communication (0.872), functionality (0.810), learning achievement (0.883), media quality and relevance (0.790), interactivity (1.000), ease of understanding (0.830), learning guidance (0.830), and concept and theory accuracy (0.776). The feasibility test produced an average percentage of 89.13%, indicating that the media was feasible for limited use. Qualitative feedback from validators suggested improving the interface, adding supporting images, and refining several presentation elements. These findings indicate that the developed Carrd–Educandy-based learning media is valid and feasible as a learning support medium for periodic table material at the development stage.